Combining host plant resistance and foliar insecticide application to manage Melanaphis sacchari (Hemiptera: Aphididae) in grain sorghum. Issue 1 (2nd January 2021) - Lahiri, Sriyanka; Ni, Xinzhi; Buntin, G. David; Punnuri, Somashekhar; Jacobson, Alana; Reay-Jones, Francis P. F.; Toews, Michael D.
Abstract: Sugarcane aphid, Melanaphis sacchari (Zehtner), recently emerged as a severe economic pest of sorghum in the USA. This insect was first discovered in the USA feeding on grain sorghum in Texas in 2013 and then rapidly spread across 19 additional states. In order to develop management practices to prevent yield loss, the objective of this study was to assess the value of host plant resistance and foliar applications of insecticide in five commercially available grain sorghum hybrids, across five locations in the southeastern USA. Field experiments were conducted in 2017 in Tift, Peach, and Pike Counties in Georgia; Barbour County in Alabama; and Darlington County in South Carolina. Foliar flupyradifurone applications were initiated at the action threshold of 50 aphids per leaf for each hybrid. Grain sorghum hybrids 'DKS48-07' and 'DKS37-07' showed resistance to M. sacchari across study locations. The most resistant variety, 'DKS48-07', required no foliar insecticide. Conversely, hybrids 'KS585' and 'DKS53-53' were highly susceptible. A single foliar application of flupyradifurone immediately suppressed M. sacchari populations and no further treatments were required.